What makes a thing abominable? Observations on the language of boundaries and identity formation from a social scientific perspective - Crouch, C.L. (Brill, 2015)
Previous attempts to synthesise biblical texts’ usage of tw‘bh have associated the language with cultic concerns in Deuteronomy and Ezekiel or with ethical concerns in Proverbs. The reconciliation of these interests, especially in conjunction with a number of additional outlier texts, has proved problematic. This investigation suggests that the texts which use tw‘bh and t‘b exhibit a persistent focus on issues of identity, on the transgression of boundaries and on perceptions of the compatibility and incompatibility of fundamental social, theological and ideological categories. This understanding goes some way towards providing an explanation of the diverse appearances of these terms across the biblical texts.